2023
DOI: 10.53663/turjfas.1266719
|View full text |Cite
|
Sign up to set email alerts
|

Effect of plant growth promoting rhizobacteria on the vase life of gerbera flowers

Abstract: In this study, the effects of three different bacterial isolates added to the vase solution on the vase life were investigated. All three bacterial isolates significantly increased the vase life of gerbera cut flowers. While the vase life of the flowers in the control solution was 3 days, this period reached up to 11 days in the flowers kept in the vase containing bacteria. Daily water uptake decreased with increasing time in vase in all treatments. Although there were some differences between treatments in te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…The emergence of antibiotic resistance in environmental microorganisms is another important challenge that may affect human life. It was demonstrated that a high concentration of bacteria in vase solutions shortens the lifespan of plants, and this issue has become one of the most important challenges confronting the agricultural industry in maintaining the viability of cut plants while coping with various bacteria . Moreover, the problems associated with the use of conventional chemical-based antibiotics stimulate the demand for novel, effective, and ecologically friendly bactericidal agents .…”
Section: Introductionmentioning
confidence: 99%
“…The emergence of antibiotic resistance in environmental microorganisms is another important challenge that may affect human life. It was demonstrated that a high concentration of bacteria in vase solutions shortens the lifespan of plants, and this issue has become one of the most important challenges confronting the agricultural industry in maintaining the viability of cut plants while coping with various bacteria . Moreover, the problems associated with the use of conventional chemical-based antibiotics stimulate the demand for novel, effective, and ecologically friendly bactericidal agents .…”
Section: Introductionmentioning
confidence: 99%